Developing Criteria for the Selection of Academic Leaders at Saudi Arabia’s Higher Education Institutions and Technical and Vocational Training Corporation - Al-abdulmenem, Fahad (DIRASAT: EDUCATIONAL SCIENCES, 2019)
This study was started in light of the researcher’s perception that the determination procedure of academic leaderships in his own country’s higher educational institutions is not based on scientific grounds, and many of the appointed academic leaders are in reality with no prior training on leadership. The study aimed to develop appropriate criteria and techniques for choosing academic leaders in Saudi higher educational institutions and Technical and Vocational Training Corporation (TVTC). The study’s sample consisted of 215 respondents with a background of deans, vice deans, chairmen of academic departments, and faculty members. These respondents came from five selected higher educational institutions such as Imam Muhammad ibn Saud Islamic University, King Saud University, Prince Sattam University, Shaqra University, and Al Majmaah University; and five technical colleges such as College of Technology in Riyadh, College of Technology in Kharj, College of Technology in Zulfi, College of Technology in AlMajmaah, and College of Technology in Alartauah. Results of the electronic survey showed that the present criteria used for selecting educational leaders require some few changes by creating a more standardized selection criteria, that depends on logical grounds. The following are the items/questions regarding “Standards for selecting academic leadership,” which were evaluated “high to very high” by both the HEIs and TVTC respondents: Having good reputation among his colleagues in the college; Efficient in his role and position; Held various managerial academic positions previously; among others mentioned in the discussion. According to the results of the study, the researcher recommended several recommendations at the end of the study.